Diversity of decapod crustaceans at the interface of unconsolidated seabed areas and rocky shores in tropical/subtropical Brazil - Fransozo, Adilson [UNESP]; Furlan, Maysa [UNESP]; Fransozo, V.; Bertini, Giovana [UNESP]; da Costa, R. C. [UNESP]; Fernandes-Goes, L. C. (Natl Inquiry Services Centre Pty Ltd, 2012)
The decapod crustacean assemblages from unconsolidated seabed areas located near rocky shores in the Ubatuba region on the south-east coast of Brazil were analysed by investigating the abundance, richness, diversity and dominance of species. The relationships of the sediment and bottom-water temperature to total species abundance, richness and diversity were also evaluated. Monthly samples were taken from January 1998 through December 1999 at sites in Ubatumirim and Mar Virado. At each locality, three areas were defined as either 'exposed', 'sheltered' or 'island'. The highest species abundance was found in the sheltered area of Ubatumirim and the exposed area of Mar Virado, and during autumn. At Ubatumirim, the highest richness occurred in the exposed area and the highest diversity near the island. At Mar Virado, the highest richness and diversity were found near the island. Autumn and winter collections yielded the highest richness but the lowest diversity. The higher diversities, which were measured near the islands and during spring and summer, were consequences of the greater evenness of the data. The areas with the highest diversity also had the most heterogeneous sediment composition, thus reinforcing the hypothesis that areas with more complex substrata support more diverse faunas.
Keywords: abundance; biodiversity; Decapoda; richness; substratum